Improvement of reinforced concrete design based on BS8110:1997 using computer aided software / Norhayati Ag. Mohamad - Ag. Mohamad, Norhayati (2005)
In the recent years, we have demonstrate the development of software for reinforced concrete design increases as well as the demand of reinforced concrete structures. Design softwares which are available in the market are costly, limited to certain type of computer operating systems and require specific knowledge to be applied especially to the new users. There will be probability of mistakes, time consuming and increasing cost of management. A ‘user friendly’ and simple type of software should be developed. Thus, by the term of ‘user friendly’ (other word; comprehensive tool), this study has done in order to improve the reinforced concrete design, to provide the alternative way to estimate reinforced concrete design and to utilize the application of a simple software; Visual Basic (VB). Significant attention has been given on the design of simply supported of rectangular beam accordance to BS 8110:1997 Code of Practice. In addition, this study can gain commercial value for implementation of design software since it can be run in any version of computers operating system and can be used by anyone even do not know much about VB.